Políticas territoriais e cidadania: programa territórios da cidadania no estado do Tocantins - Ferrari, Lucélia Maria Gonzaga Bernardes (Universidade Federal do Tocantins, 2019)
The unequal use of territory, provoked by the dictates of a globalized economy and by the historical insistence of a model of development of European origin, has resulted in poverty, forced locations in the Brazilian territory and attributed unequal values to the people by virtue of these locations. Inequality, therefore, besides social, is geographically and territorially manifested in the presence of the institutional framework and the public services available to the population in the different places of the Country. The research presented here sought to know to what extent a public policy of government, Programa Territórios of Citizenship, was able to extend citizenship to marginalized social groups of this constitutional right, in the state of Tocantins. The objective was also to understand, from the public policy, what institutional framework and services are available to the part of the population historically excluded from access to these services. For the understanding of the operationalization and the methodological and conceptual constitution that involves this process, it became necessary to understand the strategy used by the federal government to strengthen the territorial development through the implementation of a "mix" of actions that seek the dynamization of spaces in the state of Tocantins. From the analytical axes of citizenship and the use of the territory as political processes, which articulate general challenges of the development process with particularities and singularities of specific regions of the state of Tocantins, it was possible to glimpse the contribution of politics to the expansion of citizenship. The theoretical reference adopted in the research comes from authors such as Milton Santos, Iná Elias de Castro and Marcelo Lopes de Souza. The bibliographic review and the documentary research supported the presented results.